Research on the construction of "u-smart transportation system" under Artificial Intelligence technology - Wei, Yangyang; Wang, Yihan; Chang, Ying; Shi, Bingzhao; Shao, Ke (IOP conference series. Materials Science and Engineering, 2019)
Artificial intelligence technology in the wisdom of the urban traffic development research plays an important role in urban traffic IOT technology through constructing the RFID tags, sensors, camera, GPS, intelligent recognizer based on sensing based on network information platform, complete traffic IOT information perception and gathering, analysis layer will real-time information into artificial intelligence algorithms library, sample library, information processing and comparison, the urban traffic information data visualization, and get the optimal treatment scheme, feedback to the practical application of terminal, to achieve the full link operation of artificial intelligence. As the subject, "people" always interact closely with "things" and "the state of things" and "intelligent interconnection". In the process of information interaction, the urban traffic information interconnection system under the artificial intelligence technology constitutes the core hub of smart city traffic, and it becomes possible to build an intelligent city "u-intelligent transportation system".